2008
DOI: 10.1103/physrevlett.101.035301
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Pumping of Rb Atoms on He Nanodroplets via Nondestructive Optical Excitation

Abstract: We measured laser-induced-fluorescence (LIF) and beam-depletion (BD) spectra of rubidium atoms (5S-5P transition) on the surface of superfluid helium nanodroplets (M-He_{N} with M=Rb). It is known that when M is a lighter alkali atom electronic excitation always leads to detachment of the excited atom (M;{*}). The dissociation energy, few tens cm;{-1}, comes either as photon excess energy or from the barrierless formation of a M;{*}-He exciplex. We observe that this picture does not hold when M=Rb and the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
79
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 22 publications
13
79
0
Order By: Relevance
“…This observation is in line with earlier measurements of the fluorescence emissions of Na 2 molecules in triplet states, which indicated vibrational relaxation in the excited electronic state to take place on the time scale of the life time of the excited state due to spontaneous emission (∼ 10 ns) [27]. Recently, it was observed that desorption upon electronic excitation may even be completely inhibited in the case of Rb atoms excited in a particular laser wave length range [28].…”
Section: Introductionsupporting
confidence: 89%
“…This observation is in line with earlier measurements of the fluorescence emissions of Na 2 molecules in triplet states, which indicated vibrational relaxation in the excited electronic state to take place on the time scale of the life time of the excited state due to spontaneous emission (∼ 10 ns) [27]. Recently, it was observed that desorption upon electronic excitation may even be completely inhibited in the case of Rb atoms excited in a particular laser wave length range [28].…”
Section: Introductionsupporting
confidence: 89%
“…Experiments involving electronic excitations of one alkali atom adsorbed on a helium cluster are available. [7][8][9][10][11][12][13][14][15][16] Some of them focused on the spectroscopy of helium-Rb exciplex formation. [7][8][9][10] Theoretical modeling of these experiments is still a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…69 The exact value may depend on the dopant species and on the state the dopant is excited to. 27,31,70 Unfortunately, the quality of the recorded data does not allow a more detailed analysis. Future two-color pump-probe experiments will improve the signal quality by choosing appropriate probe frequencies for single-photon PI.…”
Section: The Rb 3 Trimermentioning
confidence: 99%